Advertising Strategies in Cultural Scenarios - Mena García, Enrique (2017)
Our tool is marketing subject to the incipient cultural market that is booming and that does not cease to grow and that increasingly welcomes diverse sectors of the population thanks to all the disparity of offers. This market or cultural marketing we analyze from an advertising sphere, within one of the “4 P’s” of Marketing Mix, promotion, secured with examples in museums. It is a question of placing the work or artistic piece as the axis of all this network, through which the voracious market of buying and selling of the art, cultural terrain close and distant at the same time by their ignorance and unreasonable prices. This language of art in museums is approaching the society thanks to the publicity and tries to mitigate this dualism society-museums, taking advantage of the art to attract an audience more profane or on the contrary, strengthen those who demand culture.